The department of university extension: a track without inventory in the history of Popular Education and Youth and Adult Education in Argentina (Praxis Educativa, 2017)
In the paper we present progress of a research project that aims at studying the political-pedagogical project and actions of popular education with youth and adults in the Department of University Extension of the University of Buenos Aires which ran between 1956 and 1966.The Department of University Extension attempted toarticulatethe university with the people. The focus of its actions was in the Maciel Island. There, for ten years, they developed educational, health and welfare actions in order to solve the problems of the inhabitants of the island, from a joint effort between the university and the community.
Keywords: Adult Education; University Extension; Popular Education; University of Buenos Aires; Education History